Cryptocurrencies and the future of money. Money and trust in Mexico - Seiferling, Mike; Ahmed, Thamin; ElBahrawy, Abeer Yehia; Chan, Keith; Padilha, Tales (IE Center for the Governance of Change, 2020)
As official legal tender in Mexico, Canada and the United States until the mid-1800s, the Mexican Peso is one of the oldest currencies in North America. Today, Mexico’s currency is the 15th most traded in the world, and is the the most traded of all Latin American countries1 . This reflects the strength of both the Mexican economy and it’s currency. The current denomination of the Mexican Peso comes from 1993, when, after the high inflation of the late 80s, president Carlos Gortari stripped three zeros from the Peso creating the Nuevo Peso (New Peso). In 1996, the word Nuevo (new) was removed and the currency was once again named Peso (without changing its denomination). Although Mexico faced periods of high inflation during the mid-90s, with almost 35% of annual inflation in 1995 and 1996, this can’t be compared with the hyperinflation of other Latin American countries (Argentina and Brazil) during the 90s. Therefore, we can say that, overall, since the implementation of the New Peso in 1993, Mexico’s currency has been fairly stable, helping to boost the country’s economic development in the 21st century
Keywords: Cryptocurrency; Criptomonedas; Policies; Políticas; Perspectives; Perspectivas; Disrupting economy; Disrupting economy